2019
DOI: 10.24036/humanus.v18i2.104342
|View full text |Cite
|
Sign up to set email alerts
|

Form Shifts in Translating Passive Clauses Found in Novel Harry Potter: Harry Potter and the Deathly Hallows

Abstract: Shift is one of the phenomena in translation to suit with the acceptability of translation product. This article aims at finding out the shifts of form in translating passive clauses found in the novel Harry Potter translated by Listiana Srisanti. This research used a qualitative method where the research analysis relied on linguistic description and employed meaning-based to reveal and describe how is the existence of shifts of form and meaning in the translation. The data of this research were passive clause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Kaswanti (1982: 33) mentioned that the analysis of Indonesian grammar was "colored in tradition for a long time although the tradition was already transformed". Melyanda, Jufrizal, and Yusdi (2019) found that the focused phrase maintains the front position in Indonesian while the structure shift including subject omission often occurs in natural Indonesian.…”
Section: Introductionmentioning
confidence: 97%
“…Kaswanti (1982: 33) mentioned that the analysis of Indonesian grammar was "colored in tradition for a long time although the tradition was already transformed". Melyanda, Jufrizal, and Yusdi (2019) found that the focused phrase maintains the front position in Indonesian while the structure shift including subject omission often occurs in natural Indonesian.…”
Section: Introductionmentioning
confidence: 97%